Multiple Cutaneous Melanomas - Carmen Cristina DRAGHICI; Adelina POPA; Florica SANDRU (Modern Medicine)
Cutaneous melanoma is a malignant tumor that develops from melanocytes found in the basal layer of the epidermis. Even though it is not the most common type of skin cancer, it is the most aggressive one with an increasing incidence worldwide. The risk factors inherited in the appearance of melanoma are sun exposure together with severe sunburns in childhood and adolescence, high number of moles and genetic factors. We present the case of a 66 years old women with numerous skin sunburns in the past years who refer to our clinic for three pigmented skin lesions, with asymmetrical edges, elevated to the cutaneous plane, with a diameter of 2 cm for the largest one and chromatic dysmorphism, located on the posterior thorax. The dermoscopic examination was suggestive for cutaneous melanoma. We performed the surgical excision of all three cutaneous tumors and the histopathologic examination was performed. The diagnosis of all three lesions was of melanoma. A CT examination was made together with sentinel node biopsy. The aim of this paper is to present a rare case of simultaneous three skin melanomas and the treatment alternatives of this patient after clinical and paraclinical investigations.